Circulating and cellular adiponectin in polycystic ovary syndrome: relationship to glucose tolerance and insulin action - Aroda, Vanita; Ciaraldi, Theodore P.; Chang, Sang-Ah; Dahan, Michael H.; Chang, R. Jeffrey; Henry, Robert R. (Fertility and sterility, 2008)
To evaluate serum adiponectin levels and organization into multimers in women with polycystic ovary syndrome (PCOS) and assess relationships between adiponectin, glucose tolerance, and insulin resistance. In vivo and in vitro study. Outpatient clinic at university and Veterans hospitals in the United States and university laboratory. Thirty-one obese women with PCOS and six age- and body mass index (BMI)-matched normal cycling control subjects. All subjects studied in the fasting state. A 75-g oral glucose tolerance test (OGTT), hyperinsulinemic/euglycemic clamp, circulating adiponectin levels, adipocyte adiponectin content, and organization of adiponectin into multimeric forms. Whole body insulin action (glucose disposal rate, 5.61 ± 2.90 vs. 8.79 ± 0.81 mg/kg/min, PCOS and control) and adiponectin levels (9.5 ± 0.7 7 vs. 17.4 ± 1 μg/mL, PCOS vs. control) were significantly reduced in the subjects with PCOS. There were significant correlations between glucose tolerance, insulin action, and circulating adiponectin levels in all subjects. The content of adiponectin protein was reduced in subcutaneous adipocytes from subjects with PCOS (252 ± 31 vs. 388 ± 58 arbitrary units/10 μg protein). Subjects with PCOS had less of their circulating adiponectin organized into high molecular weight (HMW) multimeric complexes. Glucose-intolerant subjects with PCOS also had less intracellular HMW adiponectin. Both circulating adiponectin levels and the portion present as the most active HMW form are reduced in PCOS, with differences related to the degree of glucose intolerance and insulin resistance.